Excavating the land of Jesus how archaeologists study the people of the gospels - Strange, James Riley 1963- (Grand Rapids, Michigan William B. Eerdmans Publishing Company, 2023)
"A textbook about the archaeology of first-century Roman Galilee and how it relates to the gospels"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Antiquities; Archaeology; Galilee (Israel) -- Antiquities